2005
DOI: 10.1007/s10517-005-0232-3
|View full text |Cite
|
Sign up to set email alerts
|

First experience in the use of bone marrow mesenchymal stem cells for the treatment of a patient with deep skin burns

Abstract: Female patient with extensive skin burn (I-II-IIIAB skin burn, total area 40%, area of IIIB degree 30%) was treated using transplantation of allogenic fibroblast-like bone marrow mesenchymal stem cells onto the surface of deep thermal burn. The study of wound healing dynamics after transplantation of allogenic fibroblast-like mesenchymal stem cells confirmed high tempo of wound regeneration in the presence of active neoangiogenesis. Due to this, autodermoplasty of burn wounds could be carried out with good res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
100
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(107 citation statements)
references
References 10 publications
5
100
0
2
Order By: Relevance
“…Preclinical human studies have investigated the effect of MSC treatment on chronic wounds, 6,7 burns, 8 radiation wounds, 9 and blistering skin disorders. 10 The results from these studies and animal models have been promising with positive outcomes on wound repair.…”
Section: Background Bone Marrow-derived Mscs Improve Wound Healingmentioning
confidence: 99%
“…Preclinical human studies have investigated the effect of MSC treatment on chronic wounds, 6,7 burns, 8 radiation wounds, 9 and blistering skin disorders. 10 The results from these studies and animal models have been promising with positive outcomes on wound repair.…”
Section: Background Bone Marrow-derived Mscs Improve Wound Healingmentioning
confidence: 99%
“…11,[15][16][17][18] Despite these immune-enhancing properties of MSCs, they have been reported to suppress immune rejection in different species, including human and nonhuman primates. [19][20][21] However, tolerance of MSCs across the allogeneic barrier might not be absolute since studies by another group report on experimental evidence that questions the status of immune privilege. 22 The expression of MHC-II expression on MSCs raises 2 concerns.…”
Section: Introductionmentioning
confidence: 99%
“…A level equal to or greater than 10 6 organism per gram of tissue is strongly related to impaired wound healing. [3][4][5][6][7] It has been demonstrated that bone marrow-derived mesenchymal stem cells (BMSCs) can promote the healing of compromised wound, 8,9 probably because of their plasticity in differentiation, 10,11 secreting cytokines and growth factors critical to wound healing, 12,13 low immunogenic property 14 and immunomodulatory function. 15 BMSCs are demonstrated to be potent carriers for exogenous genes.…”
Section: Introductionmentioning
confidence: 99%